PEMANFAATAN KEGIATAN PEMBIASAAN POSITIF DALAM MENUMBUHKAN SIKAP KEMANDIRIAN SISWA SEKOLAH DASAR SEBAGAI PENGUATAN P7 - Anggita Tresna Damayanti; Rinaldi Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Independence is one of the core dimensions of the Pancasila Student Profile that should be developed from the elementary school level through continuous character education. However, many students still demonstrate limited responsibility, dependence on teachers in completing tasks, and a lack of self-management in daily school activities. One strategy to address this issue is the implementation of positive habituation activities as part of the school's culture. This study aimed to describe the utilization of positive habituation activities in fostering the independence of fourth-grade students at MI An-Najwa as an effort to strengthen the Pancasila Student Profile. This research employed a qualitative approach using a case study method. The participants consisted of the principal, the fourth-grade teacher, and fourth-grade students selected through purposive sampling. Data were collected through observation, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings revealed that positive habituation activities, such as Qur'an recitation before class, daily prayers, congregational Dhuha and Dhuhr prayers, and the independent preparation of learning and worship materials, improved students' discipline, responsibility, and independence. Therefore, positive habituation activities contribute to strengthening the independent dimension of the Pancasila Student Profile through a consistent, sustainable, and religious school culture. Keywords: positive habituation, independence, Pancasila Student Profile.